Study on flexural stiffness of diagrid non-stiffened node based on four-spring assemblage model. (1st November 2019) - Liu, Chengqing; Luo, Xinyi; Fang, Dengjia; Shi, Chuanqing; Sarvar, Saydirakhmonov; Zhao, Bida
Highlights: Flexural stiffness of diagrid non-stiffened CFST nodes is studied. Four-spring assemblage model of CFST node and its stiffness matrix is derived. FE models of three influence factors and force-displacement skeleton curves are formed. Abstract: The flexural stiffness of diagrid non-stiffened concrete filled steel tubular (CFST) nodes are studied based on the four-spring assemblage model. Firstly, the four-spring assemblage model of CFST node is established by simplifying the node into a movable rigidity piece, a fixed rigidity piece and four springs to represent mechanical behavior. Based on the displacement and force characteristics under different loads, the stiffness matrix of the model is derived. The expressions of two kinds of undetermined parameters, such as spring position and spring stiffness, are obtained by the reverse educing method. The single variable finite element models of three influence factors are established in three different groups. Then the values of 16 undetermined parameters are derived and a large number of scattered data are obtained. Force-displacement skeleton curves are formed. Finally, the multi-parameter analysis is done and the analytic expressions of the undetermined parameters are derived according to the analysis of these scattered data. A comparative analysis between the results obtained by the finite element analysis results with those from errors calibration is conducted in-detail. The results show that the errors between the results of finite element analysis and those of the four-spring assemblage model are acceptable, which indicates that the four-spring assemblage model is suitable for reflecting the flexural stiffness of diagrid non-stiffened nodes.